Hitchhiking the high seas: Global genomics of rafting crabs. Issue 3 (23rd January 2019) - Pfaller, Joseph B.; Payton, Adam C.; Bjorndal, Karen A.; Bolten, Alan B.; McDaniel, Stuart F.
Abstract: Population differentiation and diversification depend in large part on the ability and propensity of organisms to successfully disperse. However, our understanding of these processes in organisms with high dispersal ability is biased by the limited genetic resolution offered by traditional genotypic markers. Many neustonic animals disperse not only as pelagic larvae, but also as juveniles and adults while drifting or rafting at the surface of the open ocean. In theory, the heightened dispersal ability of these animals should limit opportunities for species diversification and population differentiation. To test these predictions, we used next‐generation sequencing of genomewide restriction‐site‐associated DNA tags (RADseq) and traditional mitochondrial DNA sequencing, to investigate the species‐level relationships and global population structure of Planes crabs collected from oceanic flotsam and sea turtles. Our results indicate that species diversity in this clade is low—likely three closely related species—with no evidence of cryptic or undescribed species. Moreover, our results indicate weak population differentiation among widely separated aggregations with genetic indices showing only subtle genetic discontinuities across all oceans of the world (RADseq F ST  = 0.08–0.16). The results of this study provide unprecedented resolution of the systematics and global biogeography of this group and contribute valuable information to our understanding of how theoretical dispersal potential relates to actual population differentiation and diversification among marine organisms. Moreover, these results demonstrate the limitations of single gene analyses and the value of genomic‐level resolution for estimating contemporary population structure in organisms with large, highly connected populations. Abstract : Next‐generation sequencing of genomewide restriction‐site‐associated DNA tags (RADseq ) and traditional mitochondrial DNA sequencing were used to investigate the species‐level relationships and global population structure of Planes crabs collected from oceanic flotsam and sea turtles. Our results indicate that species diversity in this clade is low—only three species—with no evidence of cryptic or undescribed species. Moreover, our results indicate weak population differentiation among widely separated aggregations with genetic indices showing only subtle genetic discontinuities across all oceans of the world.